Antibacterial Potention and pH Analysis of Kombucha with Anna Apple (Malus domestica) Peel as Its Substrate - Lestari, Kinanti Ayu Puji; Wulansari, Silvi Ayu (Universitas Islam Negeri Mataram, 2022)
This study aimed to determine the antibacterial abilities of Kombucha with Anna apple peel as the substrate. This study was conducted on the antibacterial assay of Kombucha with the formulation of 10g (formulation A), 15g (formulation B), and 20g (formulation C) apple peels. Each formulation then made three different test concentrations of an antibacterial test by the Kirby Bauer method. There was a decrease in the pH value measured before and after fermentation of kombucha apple peel due to the production of acetic acid formed from metabolic activity between bacteria and yeast as a culture of kombucha beverage. The results of the antibacterial test showed that all of the test concentrations could inhibit the growth of the test bacteria until they were in the category of medium and high inhibition. The largest diameter of the inhibition zone was shown by formula C with a concentration of 100% (17 mm). The diameter of the inhibition zone is directly proportional to the amount of apple peel contained in the formula and the concentration of the sample being tested.